Laparoscopic right hepatectomy for hepatocellular carcinoma after sequential yttrium-90 liver radioembolization and liver venous deprivation (with video) - De Mathelin, Pierre; Addeo, Pietro (Journal of minimally invasive surgery, 2025)
Laparoscopic right hepatectomy has gained acceptance for major oncologic hepatectomies. Preoperative sequential strategies for induced tumor downsizing and contralateral liver hypertrophy ensure the safety of these major hepatectomies, especially in cases of underlying liver disease. In this video, we present a sequential minimally invasive approach used to treat a large hepatocellular carcinoma (HCC) developed in steatotic liver using sequentially yttrium-90 liver radioembolization (transarterial radioembolization), liver venous deprivation (LVD), and minimally invasive surgery. A computed tomography scan 30 days after the LVD procedure showed a future liver remnant hypertrophy rate of 89.8% and a kinetic growth rate of 5.4 mL/day. A laparoscopic right hepatectomy was then performed. Postoperative course was uneventful with bilirubin normalization at postoperative day 2. Patient was discharged on postoperative day 8. In case of voluminous HCC on steatosis liver, we provide an innovative combination of preoperative liver radioembolization and LVD to generate maximal liver hypertrophy and to allow a safe laparoscopic right hepatectomy.